Green innovation, business opportunities and managerial environmental concern in the performance of Jordanian agri-food firms: a conceptual framework - Qatanani, Nour Othman; Keshminder, J.S.; Arshad, Azlin Shafinaz (Faculty of Business and Management, 2025)
The agri-food sector in developing countries like Jordan plays a critical role in economic development but faces growing environmental challenges due to resource inefficiencies, ecological degradation, and increasing sustainability pressures. Green innovation (GI) has emerged as a vital strategy to enhance both environmental and financial performance. However, existing research has largely overlooked how the dimensions of GI, namely green product, green process, and green organizational innovation, interact with internal and external drivers in low-technology, resource-constrained sectors. In particular, the mediating role of business opportunities and the moderating role of managerial environmental concern remain underexplored. To address this gap, this conceptual study proposes an integrative framework that synthesizes insights from the Porter Hypothesis, Ecological Modernization Theory, the Resource-Based View, the Natural Resource-Based View, Stakeholder Theory, and Institutional Theory. The framework incorporates four key drivers: market demand, environmental collaboration, regulation, and firm capabilities, and examines their influence on the three dimensions of GI. It also positions business opportunities as a mediating mechanism and managerial environmental concern as a moderating factor in the relationship between GI and firm performance. Tailored to the context of Jordan’s agri-food sector, the proposed model offers a foundation for future empirical research and provides strategic insights for firms and policymakers seeking to advance sustainable innovation in developing economies.